Estimation of Demand System for Household Energy Consumption: Empirical Evidence from Indonesia - Rasyid, Mohtar; Kristina, Anita (International Journal of Energy Economics and Policy, 2021)
This study aims to estimate the pattern of household demand for energy consumption such as electricity, water and fuel. The data used in this study is the publication of the Indonesia Family Life Survey (IFLS). To obtain comprehensive estimation results, this study uses the Quadratic Almost Ideal Demand System (QUAIDS) approach which is currently the standard in household demand estimation systems. The unit of observation used in this paper is more than three thousand households representing 13 provinces in Indonesia. The results show that the largest household energy consumption expenditure is electricity consumption followed by fuel and water. However, unlike the case of other commodities, the elasticity of spending on electricity is negative. Thus, an increase in household income will shift spending from electricity to consumption of other goods such as fuel, water and others. Meanwhile, the price elasticity for all energy commodities is inelastic. The increase in energy consumption commodity prices did not change demand much. This means that households are still very dependent on the supply of energy goods produced by the government. Therefore, appropriate policies are needed in determining the basic electricity tariff, fuel prices and clean water supply so that basic household needs can be fulfilled. Keywords: Energy Consumption, System Demand, Household Expenditure, QUAIDS JEL Classifications: D12, Q41, R20 DOI: https://doi.org/10.32479/ijeep.11714